Analisis Kesulitan Belajar IPA Peserta Didik pada Masa Pandemi Covid-19 di SMPN 2 Batang Anai - Erlinda, Nelfi; Lelfita; Musrial (LP. Ma'arif Janggan Magetan, 2022)
This study aims to determine: 1) Difficulties in learning science for students at SMPN 2 Batang Anai 2) Factors that cause difficulties in learning science for students at SMPN 2 Batang Anai during the covid-19 pandemic, 3) efforts made to overcome difficulties learning science for students at SMPN 2 Batang Anai during the covid-19 pandemic. The population in this study were all students of SMPN 2 Batang Anai for the academic year 2020/2021. The sample technique in this study was taken using a random sampling technique. The research instrument that the researcher uses is in the form of a questionnaire or a questionnaire given to the sample and documentation. The analytical technique used is statistical test analysis technique. Statistical tests are used to see the accuracy or accuracy of an equation function to estimate the data that we analyze. The results of this study indicate that students' learning difficulties in science at SMPN 2 Batang Anai during the COVID-19 pandemic were categorized as low with a percentage of 28.25% with a score of 21% -40%.